PENGARUH PEMBERIAN LIMBAH MEDIA JAMUR TIRAM (Pleurotus ostreatus (Jacq)P.Kumm) TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Setia Ayu Lestari; Umrah Umrah; Miswan Miswan (Biocelebes, 2016)
The  growth of cocoa plant seedlings (Theobroma cacao L.) can be Increased by using organic material, for examples oyster mushroom media waste (Pleurotus ostreatus (Jacq)P.Kumm). The purpose of this study was to determine the effect of oyster mushroom media waste on the growth of cocoa plant seedlings. This study was conducted during period of March until May 2015. Cocoa plant seeds was planted in plastic bags with size 30 x 40 cm, designed in a Completely Randomized Design (CRD). The treatment consists of P0 (soil media without oyster mushroom media waste, as a negative control);P1 (soil media is 90% + oyster mushroom media waste is 10%), P2 (soil media is 80%+ oyster mushroom media waste 20%), P3 (soil media is 70% + oyster mushroom media waste 30%), P4 (soil media is 60% + oyster mushroom media waste is 40%), P5 (soil media is 50% + oyster mushroom media waste 50%), P6 (soil media is 3 kg + NPK Fertilizer is 3 g, as a positive control).The observation parameters includes the plants high, number of leaves, stem diameters, plants fresh biomass and plants dry biomass. The results was showed that the best tretment is P2 acording there are average parameters,  include 24,63 cm high of plant; 10,66 number of leaves; 0,42 cm stem diameters; 4,73 grams of fresh biomass and 2,15 grams of dry biomass.                      Keywords : Cocoaseedlings, oyster mushroom media waste (Pleurotus ostreatus (Jacq)  P.Kumm), Theobroma cacao L.